2021
DOI: 10.1159/000515900
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Transfusion and Outcomes of Preterm Infants: A Cross-Sectional Study

Abstract: <b><i>Background:</i></b> Prophylactic platelet transfusion has been adopted as a ubiquitous practice in management of thrombocytopenia in preterm infants to reduce the risk of bleeding. <b><i>Objectives:</i></b> The objectives of this study were to report the prevalence of platelet transfusion among preterm infants with thrombocytopenia and to assess the association of platelet transfusion with mortality and morbidity in this population. <b><i>Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…This analysis demonstrated that neonates with the highest baseline risk of bleeding/mortality (based on accepted clinical factors such as gestational age, underlying diagnosis, etc) benefitted just as much as low‐risk neonates from the restrictive transfusion thresholds. While these findings seemed surprising at first, they were in fact consistent with several observational studies that had found a poor correlation between platelet count and bleeding risk (suggesting that factors other than platelet count are better predictors of bleeding risk in neonates), 7,11–14 no effect of platelet transfusions in reducing the incidence or severity of IVH, 8,12,15 and an association between number of platelet transfusions and increased neonatal morbidity and mortality 16–22 …”
Section: Thrombocytopenia and Platelet Transfusions In Neonatessupporting
confidence: 78%
See 1 more Smart Citation
“…This analysis demonstrated that neonates with the highest baseline risk of bleeding/mortality (based on accepted clinical factors such as gestational age, underlying diagnosis, etc) benefitted just as much as low‐risk neonates from the restrictive transfusion thresholds. While these findings seemed surprising at first, they were in fact consistent with several observational studies that had found a poor correlation between platelet count and bleeding risk (suggesting that factors other than platelet count are better predictors of bleeding risk in neonates), 7,11–14 no effect of platelet transfusions in reducing the incidence or severity of IVH, 8,12,15 and an association between number of platelet transfusions and increased neonatal morbidity and mortality 16–22 …”
Section: Thrombocytopenia and Platelet Transfusions In Neonatessupporting
confidence: 78%
“…While these findings seemed surprising at first, they were in fact consistent with several observational studies that had found a poor correlation between platelet count and bleeding risk (suggesting that factors other than platelet count are better predictors of bleeding risk in neonates), 7 , 11 , 12 , 13 , 14 no effect of platelet transfusions in reducing the incidence or severity of IVH, 8 , 12 , 15 and an association between number of platelet transfusions and increased neonatal morbidity and mortality. 16 , 17 , 18 , 19 , 20 , 21 , 22 …”
Section: Thrombocytopenia and Platelet Transfusions In Neonatesmentioning
confidence: 99%
“…Another publication found that platelet transfusion was associated with higher risks of arterial thrombosis and mortality among thrombotic thrombocytopenic purpura (TTP) and heparin-induced thrombocytopenia (HIT) patients [29]. A crosssectional study reported that platelet transfusion was associated with increased mortality and comorbidities in premature infants with thrombocytopenia [30]. In addition, platelet transfusion rates were associated with hospital mortality (adjusted relative risk per 5 ml/kg/d increase:…”
Section: Discussionmentioning
confidence: 99%
“…Another publication found that platelet transfusion was associated with higher risks of arterial thrombosis and mortality among thrombotic thrombocytopenic purpura (TTP) and heparin‐induced thrombocytopenia (HIT) patients [29]. A cross‐sectional study reported that platelet transfusion was associated with increased mortality and comorbidities in premature infants with thrombocytopenia [30]. In addition, platelet transfusion rates were associated with hospital mortality (adjusted relative risk per 5 ml/kg/d increase: 1.12; 95% CI 1.02–1.23, p = 0.02) among neonates receiving extracorporeal membrane oxygenation (ECMO) [31].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In the US, 23% of preterm infants with thrombocytopenia received platelet transfusion. 3 However, whether these transfusions are beneficial or detrimental is still controversial.…”
Section: Introductionmentioning
confidence: 99%